Conversion of atrial fibrillation to sinus rhythm during cryoballoon ablation: A favorable and not unusual phenomenon during second‐generation cryoballoon pulmonary vein isolation. Issue 2 (16th January 2020) - Maj, Riccardo; Borio, Gianluca; Osório, Thiago G.; Iacopino, Saverio; Ströker, Erwin; Sieira, Juan; Terasawa, Muryo; Rizzo, Alessandro; Scala, Oriana; Galli, Alessio; Varnavas, Varnavas; Paparella, Gaetano; et al.
Abstract: Background: The prevalence and the clinical impact of conversion of atrial fibrillation (AF) to sinus rhythm (SR) during cryoballoon ablation (CB‐A) are unknown. Objective: The purpose of this study was to evaluate the prevalence of restoration of SR during CB‐A and the clinical impact of this phenomenon. Methods: Between January 2012 and September 2018, all patients who experienced conversion of AF to SR during CB‐A were included. This group was subsequently matched for gender, age, type of AF, diagnosis‐to‐ablation time, and left atrial size with patients who underwent CB‐A and did not experienced conversion of AF to SR. After discharge, patients were scheduled for follow‐up visits at 1, 3, 6, and 12 months and 24 hours Holter recordings were obtained at each follow‐up visit. All documented AF episodes of >30 seconds were considered as recurrence. A 3 month post‐procedural blanking period (BP) was applied. Results: A total of 1559 patients underwent pulmonary veins isolation by CB‐A between January 2012 and September 2018; among them, 58 patients (3.7%) experienced restoration of SR during CB‐A. In total, 53 patients (41 males [77.3%], mean age 61.4 ± 13.3 years) were included in the case group. During CB‐A, restoration of SR occurred more frequently during right‐side PVs applications (right inferior pulmonary vein 39.6%, right superior pulmonary vein 30.2%). If considering a BP, at 2 year follow‐up, freedom from recurrences was 86.5% in the case group and 68.0% in the control group ( P = .036). Conclusion: Conversion of AF to SR is a favorable and relatively frequent phenomenon during cryoballoon pulmonary vein isolation ablation. Abstract : Our paper shows that conversion of atrial fibrillation to sinus rhythm is not an anusual phenomenon during cryoballoon pulmonary vein isolation ablation, and it is associated with a very good outcome at a mid‐term follow‐up.